Embitterment: Societal, psychological, and clinical perspectives - Linden, Michael (SpringerLink Bücher, 2011)
Embitterment is a distinct state of mood known to everyone. It can be seen in the context of exceptional though 'normal' negative life events. It is an emotional reaction e.g. to humiliation, to being severely disappointed by others, or to violations of basic values. Embitterment is accompanied by other emotions like feelings of hopelessness and helplessness, poor moods and a lack of drive, and aggression towards oneself and others. It can end in suicide or even murder-suicide and in a distinct pathological state known as 'Posttraumatic Embitterment Disorder (PTED)'. But despite the high preva